Technological Competencies among Physical Education Teachers in the Digital Era - Asi, Amani; Sabbah, Suheir (Journal of Technical Education and Training, 2025)
In response to worldwide moves toward digital education, this cross-sectional study looks at the technological competencies of physical education teachers in Palestine—a setting where such research is still rare. Data were obtained from 55 physical education instructors in the Ramallah Governorate using a validated, high-reliability questionnaire (Cronbach's alpha > 0.91). Three areas—technological literacy and usage, educational technology applications, and e-learning competencies—were evaluated in this paper. The results demonstrate a high level of technological competency, with no significant differences based on gender, school type, or years of experience. Lower proficiency was observed, nevertheless, in using modern technologies such virtual reality and collaborative learning environments. This study underlines the need of focused professional development to close gaps in advanced technology use and adds new perspectives on the digital readiness of physical education teachers in under-resourced environments. The results guide curriculum designers and policy-makers on areas needing assistance in programs for teacher preparation.